Stated choice model of transport modes including solar bike - Pauline van den Berg; Suzette Vinken; Karst Geurs; Theo Arentze (Journal of Transport and Land Use)
In the Netherlands, e-bike ownership and use has rapidly increased over the last decade. A new type of e-bike, the solar bike, has recently been developed. The solar bike is an electric bike with solar panels in the front wheel that charges through sunlight. The aim of this study is to gain more insight in the factors affecting people’s choice between different transport modes, including car, public transport, regular bike, e-bike and solar bike. Based on a stated choice experiment among 308 respondents, a mixed logit error components model for transport mode choice was estimated. The results show that the solar bike is preferred for medium-length trips during daylight and in good weather. Land-use attributes such as good bike lanes, secured bike parking, congested roads and paid parking also have a positive effect on choosing a solar bike over a car. In addition, a latent class model was estimated to segment respondents according to their base preferences for transport modes. Three segments were identified: a segment with a preference for the solar bike, a segment of car lovers and a segment with a preference for public transport and a regular bike. Chi-square and ANOVA tests show that solar bike affinity is related to being female, older, Dutch, and having a positive attitude toward e-bike, solar bike, innovation and the environment.